Comparison of the Effectiveness of Acceptance and Commitment Therapy and Transdiagnostic Therapy on Interpersonal Guilt and Emotional Inhibition in Patients with Multiple Sclerosis - Navaei, Mojgan; Fakhri, Mohammad Kazem; Mirzaian, Bahram (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The aim of the present study was to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Transdiagnostic Therapy on interpersonal guilt and emotional inhibition in patients with Multiple Sclerosis (MS).Methods and Materials: The study employed a quasi-experimental design with pre-test, post-test, and follow-up phases, including a control group. The research population consisted of all women aged 20 to 40 years with MS who were members of the MS Association of Amol in the first half of 2023. The research sample included 48 individuals with MS who were selected through simple random sampling and were randomly assigned to two experimental groups and one control group. The research instruments included the Interpersonal Guilt Scale by Gazzillo et al. (2018) and the Emotional Inhibition Scale by Kellner (1986). Data were analyzed using repeated measures analysis of covariance (ANCOVA) and Bonferroni post-hoc tests with SPSS version 24 software.Findings: The results indicated significant differences between the effects of ACT, Transdiagnostic Therapy, and the control group on the variables of interpersonal guilt and emotional inhibition (P < 0.05). Furthermore, post-hoc test results revealed that Transdiagnostic Therapy had the most significant therapeutic effects on improving emotional inhibition in patients with MS compared to ACT. The two-month follow-up confirmed the stability of the study's results.Conclusion: The effectiveness of both therapeutic approaches suggests that clinicians and treatment teams can utilize psychological treatment approaches alongside biological treatments to reduce the severity of psychological and emotional symptoms resulting from chronic illnesses, thereby facilitating the treatment process.